2011
DOI: 10.1111/j.1469-7580.2011.01392.x
|View full text |Cite
|
Sign up to set email alerts
|

Fate of neuron-glia synapses during proliferation and differentiation of NG2 cells

Abstract: Progenitor cells expressing proteoglycan NG2 (also known as oligodendrocyte precursor cells or polydendrocytes) are widespread in the grey and white matter of the CNS; they comprise 8-9% of the total cell population in adult white matter, and 2-3% of total cells in adult grey matter. NG2 cells have a complex stellate morphology, with highly branched processes that may extend more than 100 lm around the cell body. NG2 cells express a complex set of voltage-gated channels, AMPA ⁄ kainate and ⁄ or c-aminobutyric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 110 publications
1
25
0
Order By: Relevance
“…While there is evidence for GABA A OPCs receive input from several glutamatergic and/or GABAergic axons, which disconnect when the OPCs develop into premyelinating oligodendrocytes (124,208,448). Such direct neuronal control of OPCs persists even in the mature brain (124).…”
Section: A Glutamate and Gabamentioning
confidence: 98%
See 2 more Smart Citations
“…While there is evidence for GABA A OPCs receive input from several glutamatergic and/or GABAergic axons, which disconnect when the OPCs develop into premyelinating oligodendrocytes (124,208,448). Such direct neuronal control of OPCs persists even in the mature brain (124).…”
Section: A Glutamate and Gabamentioning
confidence: 98%
“…Such direct neuronal control of OPCs persists even in the mature brain (124). It may underlie the experienceinduced changes in myelination, indicated by increased fractional anisotropy observed in the human brain by diffusion tensor magnetic resonance imaging.…”
Section: A Glutamate and Gabamentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the recorded current is hypothesized to be from both progeny cells. Second, morphological analysis indicated that each daughter cell has approximately half the number of glutamic acid decarboxylase 65- (GAD65-) positive putative GABAergic terminals in the parent cell [21, 88]. Altogether, these data indicated that NG2 cells are continuously kept functional; certain synaptic contacts are passed onto the resulting progenies during cell division.…”
Section: Neuron-ng2 Cell Synapses In Cnsmentioning
confidence: 99%
“…Before the formation of a functional myelin sheath, NG2 cells passes through two developmental stages, namely, premyelinating oilgodendrocytes and mature oligodendrocytes [8, 95, 96]. During the process of NG2 cell differentiation, the synaptic communication between neurons and NG2 cells is rapidly lost (Figure 5) [87, 88]. The differentiation of NG2 cells is characterized by the expression of stage-specific proteins, which are finely tuned by a series of transcription factors and accompanied by the expression of specific molecular markers [8, 9799].…”
Section: Neuron-ng2 Cell Synapses Are Rapidly Decreased During Celmentioning
confidence: 99%